2007
DOI: 10.18060/143
|View full text |Cite
|
Sign up to set email alerts
|

Institutionalization: A Theory of Human Behavior and the Social Environment

Abstract: Institutionalism is the syndrome first recognized and described in inpatient psychiatric facilities,which is now used to describe a set of maladaptive behaviors that are evoked by the pressures of living in any institutional setting. This article traces the development of the theory of institutionalization, which predicts and explains an individual’s response to that particular type of environment. The article makes note of key contributors and contributions, and of empirical studies that have advanced the the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(11 citation statements)
references
References 59 publications
0
10
0
1
Order By: Relevance
“…It might be the case that children were already different before they entered an institution or family. A review of empirical studies on institutionalization revealed a number of variables that may explain the poorer adjustment among institutionalized children (46), such as impaired physical health or developmental delay that might be caused or augmented by the pre-institutionalization rearing situation. Severe social and mental health problems or alcohol and drug abuse of parent(s) more likely leads to child abandonment or neglect and finally to a separation of the child from his or her parents.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It might be the case that children were already different before they entered an institution or family. A review of empirical studies on institutionalization revealed a number of variables that may explain the poorer adjustment among institutionalized children (46), such as impaired physical health or developmental delay that might be caused or augmented by the pre-institutionalization rearing situation. Severe social and mental health problems or alcohol and drug abuse of parent(s) more likely leads to child abandonment or neglect and finally to a separation of the child from his or her parents.…”
Section: Discussionmentioning
confidence: 99%
“…The genocide against the Tutsi, severe poverty, and HIV/AIDS have had devastating consequences for the functioning of families and the larger community. They have damaged the social networks that once facilitated healthy child rearing (46, 47). Given this background, the current study sheds light on the effects of institutionalization and losing parents on the psychological adjustment of children in a poor and traumatized social environment.…”
Section: Introductionmentioning
confidence: 99%
“…The trend of placing citizens in long-term care facilities and prisons is likely to rise as long as people are living longer and society is fixated on its use of incarceration as a solution to socio-economic problems (Davis, 2003;McNown Johnson & Rhodes, 2007). As total institutions (Goffman, 1961), these establishments continue to maintain a system whereby groups of people are bureaucratically processed, whilst being physically isolated from wider society by being required to sleep, work and play within the confines of the same institution.…”
Section: Socio-historical Context Of Institutionsmentioning
confidence: 99%
“…The culture of total institutions is one in which individuals lose incentive to take responsibility for their basic needs because they are relieved of the need to think for themselves (Martin, 1955;McNown Johnson & Rhodes, 2007). This process of "disculturation" can cause people to be incapable of functioning in the world beyond the institution (Goffman, 1961).…”
Section: Living In a Total Institutionmentioning
confidence: 99%
See 1 more Smart Citation